"Leksikalni arzenal" Vladimirja Pogačnika - Požgaj-Hadži, Vesna (Linguistica (Ljubljana), 2013)
Academic discourse is marked by features such as rationality, strictness, objectivity, terminological accuracy, grammatical correctness, syntactic complexity etc., as well as by various rhetorical strategies which make it recognizable as such. Rhetorical strategies serve to perpetuate various myths of the academic discourse: the myth of the researcher's objectivity, the myth of the neutrality of language resources and the myth of the absence of emotional and expressive resources. These myths and/or prejudices about the author's absolutely objective position, the neutrality of language resources and the absence of marked lexis are refuted on the basis of an analysis of Vladimir Pogačnik's academic style. Pogačnik's texts are unusual for academic discourse because the author's personal style surpasses "prescribed" rhetorical strategies, which is evident in the choice of language resources and especially of its marked lexis. We conclude that his texts alternate between what is semantically relevant and what is stylistically relevant. This confirms that the neutrality of the author's style in academic writing is nothing but yet another myth.
Keywords: akademiki; besedišče; discours académique; Pogačnik, Vladimir, 1943-; retorične strategije; Slovene; slovenski jezikoslovci; slovenščina; stilistika; stratégies rhétoriques; stylistics; stylistique; vocabulaire